A case series of forearm compartment syndrome complicating transradial cardiac catheterization - Khirul Ashar, Nur Ayuni; Ismail, Imma Isniza; Lingam, Rahul; Mazlan, Naadira Faa’iza; Azmi, Nur Syahirah (Springer Science and Business Media Deutschland, 2024)
Background: Acute compartment syndrome following a transradial coronary approach is rare. However, as the incidence of coronary arterial disease increases due to lifestyle factors and multiple comorbidities, transradial coronary angiography has become more common for diagnostic and therapeutic purposes in cardiovascular centers. Despite its rarity, we encountered two cases of acute compartment syndrome within a 1-week interval in the cardiology unit of a tertiary hospital. Case presentation: The first case involved a 75-year-old woman diagnosed with non-ST elevation myocardial infarction (NSTEMI). A coronary angiogram was performed via an uncomplicated right radial artery puncture. Following the procedure, the patient experienced significant swelling in the right forearm. An emergency fasciotomy release of the right forearm was conducted, revealing a gushing hematoma upon entering the flexor compartment. Fortunately, the wound healed well two months postoperatively with no functional deficits. In the second case, an 80-year-old man presented with severe angina pectoris upon exertion and was diagnosed with NSTEMI. The following day, he developed compartment syndrome in the left forearm, necessitating an emergency fasciotomy. Intraoperative examination revealed muscle bulging within the forearm compartments accompanied by extensive hematoma. Postoperatively, a deranged coagulation profile caused oozing from the wound. However, since there was no arterial bleeding, a compression dressing was applied. This led to a gradual drop in hemoglobin levels and worsened his heart condition. Despite resuscitative efforts and attempts to correct the coagulopathy, the patient experienced cardiorespiratory arrest and succumbed to ischemic heart disease in failure. Conclusion: Clinicians must remain vigilant in identifying this potentially limb-threatening condition. Patients with pre-existing anticoagulant therapy and underlying atherosclerotic disease are at a higher risk of bleeding complications. Implementing effective hemostasis techniques and promptly managing swelling can help prevent the occurrence of compartment syndrome. Timely assessment and maintaining a high level of clinical suspicion are paramount. If necessary, early consideration of decompressive fasciotomy is essential to avert catastrophic outcomes.